Sistem Pengamanan Ganda Pada Kendaraan Bermotor Menggunakan Kartu Secara Elektronik Berbasis Mikrokontroler - Abdi Darmawan; - Nurfiana (IIB Darmajaya, 2010)
Multiple security systems in motor vehicles in Indonesia today is required to reduce vehicle theft by people who are not responsible. Current conditions, vehicle theft rates continue to rise. The data obtained from multiple information media, both print and electronic media. Even the theft of motor vehicles had entered the campus environment. The idea how to make the vehicle security system, although there is now a double security on the vehicle include a remote that is connected with an alarm is limited to the open door, an additional lock on the wheels of motor vehicles, power down with the manual switch button and so forth. This research will be how to generate the security of two-wheeled motor vehicles especially effective and much cheaper if produced. The equipment will be made can be displayed by the LCD (Liquid Crystal Display), an attractive and easy to modify the card as a password. How it works two-wheeled vehicle security system is by entering the card as an input to turn off the alarm signal received from signal input through the motion sensor (switch). If the two-wheeler handlebar position changed from the initial position, and handlebar changed by force then it will give input to the microcontroller to inform the infrared sensor (input card), if the card is wrong then the microcontroller will activate the horn Keyword : LCD, Microcontroller, LED, motion sensor